ANALISIS UPAYA GURU DALAM MENGHADAPI ANAK BERKESULITAN BELAJAR DI TK NEGERI PEMBINA PONTIANAK BARAT - Sari, Wiwin Purnama; Miranda, Dian; Lukmanulhakim, Lukmanulhakim (Universitas Tanjungpura, 2024)
The research aims to describe the analysis of teachers' efforts in dealing with children with learning difficulties at Pembina Pontianak Barat Kindergarten. Descriptive qualitative research methodology is used. The group B class teacher at Pembina Pontianak Barat Kindergarten is the focus of this study. Interviews, observations, and documentation were the methods used for this study's data gathering. Data analysis was done, including gathering data, reducing it, presenting it, and generating conclusions. Triangulation is a method for validating data. The findings of this study are: 1. Teacher's efforts to communicate in conveying things related write reading the beginning of using examples of sentences and vocabulary that is easy for children to imitate and understand. 2. Efforts in refraction are made by teacher